The genesis of I- and S-type granitoid rocks of the early Ordovician Oledo pluton, Central Iberian Zone (Central Portugal) - Antunes, I.M.H.R. (2011)
The genesis of I- and S-type granitoid rocks of the early Ordovician Oledo pluton, Central Iberian Zone (Central Portugal)